Exploring the dynamics of playing for knowledge: Unveiling students’ intentions towards gamification adoption in Oman’s higher education institutions - Shaukat, Muhammad Rehan; Kukreti, Mohit; Jain, Vishal; Aziz, Muhammad Faisal; Sakiti, Mohammed Khamis Al (International Journal of Innovative Research and Scientific Studies, 2025)
The study investigates the adoption of gamification in Omani higher education institutions (HEIs) and its effect on student engagement, behavioral outcomes, and learning outcomes. Gamification is driven by adding interactive and motivational components that are standard in games, including points, leaderboards, badges, and challenges. The research fills the gap in the literature relating to gamification adoption in Omani higher education. Despite increasing global interest in gamification in educational contexts, this domain is poorly researched. The quantitative research design is employed by surveying 148 students enrolled in different HEIs in Oman. The questionnaire measures levels of gamification influencing behavioral and learning outcomes. In addition, the research looks at how engagement acts as a mediator along with gamified tool usability and design, and the perceived value as a moderator in improving learning. The results from this study suggest that gamification has a strong, positive impact on both behavioral and learning outcomes, with engagement discovered to be a key mediator. The moderating effects of usability and design, as well as the perceived value of gamification tools, were also found to be significant. Policymakers and educators should emphasize the alignment of gamification with Oman Vision 2040’s digital transformation goals.